Peningkatan Kemampuan PemahamanKonsep Matematika Dengan Menggunakan Model M-A-S-T-E-R Pada Siswa Kelas VIII3 SMPN 2 Lubuk Basung - Asrina Mulyati (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The result of Math subject of the students’ of SMPN 2 Lubuk Basung is still unsatisfied. Base on the data, they still get difficulties in understanding the concept. It is because of the unvariety method. The objective this research is to increase the ability in understanding the concept by using the M-A-S-T-E-R Model. This is the classroom action research (PTK) that done in two cycles of the odd semesters year of study 2010/2011. The subject is the student of VIII-3 of SMPN 2 Lubuk Basung consists of 37 students with heterogeneo usability levels. Each cycles consists of four steps; Planning, Doing, Observing, and Reflecting. To get the data is needed four instrument; observation sheets, the result test, field notes and activity documents. The data analogies used is descriptive analysis. The research report that, learning by using M-A-S-T-E-R Model to a circle material can improve understanding the concept, the students get 81,08%. Based on the classroom action research we can get a conclusion that learning by using M-A-S-T-E-R Model improve understanding the concept at the VIII3 class of SMPN 2 Lubuk Basung